Review of the Protective Mechanism of Curcumin on Cardiovascular Disease - Yang C; Zhu Q; Chen Y; Ji K; Li S; Wu Q; Pan Q; Li J (Dove Medical Press, 2024)
Chunkun Yang,1,* Qinwei Zhu,2,* Yanbo Chen,3,* Kui Ji,2 Shuanghong Li,2 Qian Wu,1 Qingquan Pan,2 Jun Li1 1Department of Cardiology, Guang'anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, People's Republic of China; 2Department of Emergency, Weifang Hospital of Traditional Chinese Medicine, Weifang, Shandong, People's Republic of China; 3Department of Arrhythmia, Weifang People's Hospital, Weifang, Shandong, People's Republic of China*These authors contributed equally to this workThese authors contributed equally to this workCorrespondence: Jun Li, Email gamyylj@163.comAbstract: Cardiovascular diseases (CVDs) are the most common cause of death worldwide and has been the focus of research in the medical community. Curcumin is a polyphenolic compound extracted from the root of turmeric. Curcumin has been shown to have a variety of pharmacological properties over the past decades. Curcumin can significantly protect cardiomyocyte injury after ischemia and hypoxia, inhibit myocardial hypertrophy and fibrosis, improve ventricular remodeling, reduce drug-induced myocardial injury, improve diabetic cardiomyopathy(DCM), alleviate vascular endothelial dysfunction, inhibit foam cell formation, and reduce vascular smooth muscle cells(VSMCs) proliferation. Clinical studies have shown that curcumin has a protective effect on blood vessels. Toxicological studies have shown that curcumin is safe. But high doses of curcumin also have some side effects, such as liver damage and defects in embryonic heart development. This article reviews the mechanism of curcumin intervention on CVDs in recent years, in order to provide reference for the development of new drugs in the future.Keywords: curcumin, intima, endothelial cells, vascular smooth muscle cell, cardiovascular diseases, inflammation, apoptosis